Yesus Kristus sebagai Imam Besar dan Implementasinya Menurut Ibrani 7:24-28 - Markus Taihuttu (Sekolah Tinggi Teologi Injili Jakarta, 2021)
This article is an attempt to prove the authenticity of the priesthood of Jesus Christ as the High Priest, which needs to investigate and explain the concept based on biblical data and facts. A strong reference to the priesthood of Jesus Christ is described in Hebrews 7: 24-28. In the Hebrews it is fully explained about the priesthood of Jesus Christ (Heb 6-9), compared to the rest of the Bible. Jesus Christ fulfilled the criteria as the High Priest even though it belonged to the tribe of Judah. Even his priesthood exceeds all the high priests of the old covenant. This is due to His eternal condition so that His priesthood is eternal as well. As for the Old Testament priests, everything is temporary. All the old high priests of the Old Testament are actually images of the priesthood of Jesus Christ as the true High Priest. AbstrakArtikel ini merupakan upaya pembuktian keabsahan keimamatan Yesus Kristus sebagai Imam Besar Agung, dimana perlu penyelidikan dan penjelasan konsep tersebut berdasarkan data dan fakta Alkitab. Referensi yang kuat tentang keimamatan Yesus Kristus dijelaskan dalam surat Ibrani 7:24-28. Dalam surat Ibrani dijelaskan secara lengkap tentang keimamatan Yesus Kristus (Ibr. 6-9), dibandingkan dengan bagian lain di seluruh Alkitab. Yesus Kristus memenuhi kriteria sebagai Imam Besar walaupun berasal dari suku Yehuda. Bahkan keimamatan-Nya jauh melebihi semua imam besar pada masa perjanjian lama. Hal ini disebabkan oleh keadaan-Nya yang bersifat kekal sehingga keimamatan-Nya bersifat kekal pula. Sedangkan para imam Perjanjian Lama, semuanya bersifat sementara. Semua imam besar perjanjian lama sebenarnya merupakan gamba-ran dari keimamatan Yesus Kristus sebagai Imam Besar yang sesungguhnya.